CIA manipulating arm of the U. S. foreign policy - "Yajee, Sheel Bhadra" (New Delhi, 1987)
This book covers the following topics: The CIA in the U.S. foreign policy planning system; The CIA push for global domination; The CIA in the U.S.- a force for suppression of political opposition;The CIA interferes in the presidential elections; The CIA takes to terrorism; Pot-shots at India; The CIA in and around Afghanistan; The CIA in Africa; Central America: The CIA terrorists and mercenaries;The CIA in the Domain of God; The CIA mission and voluntary Organizations: The CIA in handling labour; The CIA in High Finance; The CIA in black Finance and The CIA in the Macabre etc
Keywords: Espionage United States